Dosis de fertilizante Foliar con Zinc en el cultivo de Rosas de corte (Rosa sp.) a campo abierto en el distrito de Lamas - Región San Martín - Pinedo Macedo, Arturo (2016)
The rose is considered from ancient times as the queen of flowers, in which they were considered as a symbol of beauty by Babylonians, Syrians, Egyptians, Romans and Greeks. There are about 200 botanical species of roses native to the northern hemisphere, although the actual quantity is unknown due to the existence of hybrid populations in the wild. The flowers come in a wide range of colors such as red, white, pink, yellow, lavender, etc., with different shades and shades and are born on thorny and vertical stems. Roses are the most sold flowers in the world, followed by chrysanthemums, tulips, carnations and lilium. The main markets for roses are Europe, with Germany at the top, the United States and Japan. The cultivation of the rose is a very specialized crop that occupies large areas of greenhouse in Italy, Holland, France, Spain, and to a lesser extent in Israel and Germany. South American countries have increased their production in recent years, notably Mexico, Colombia and Ecuador. In Peru the production of roses has been increasing especially in the areas of the mountains and coast such as: Huancayo, Tarma, Huaral, Huaraz and Lima; The region San Martín, especially the district of Lamas, apparent microclimates for the production of this crop is that we started the present work, trying to produce for the demands of the market. Zn is a micronutrient that is required in small quantities and is related With most functions of basic plant regulation. In general terms, the action of Zn on plants involves activating various enzymatic processes. Thus, one of the most important roles attributed to Zn within the plant is related to the synthesis of tryptophan that is the precursor of auxin, a hormone that plays a fundamental role in the growth of leaves, shoots and fruits. In the present work, doses of foliar fertilizer with zinc in the cultivation of cut roses (Rosa sp) in open field in the district of Lamas - San Martín Region, the cultivation of roses presents a unique problem that is the appearance of stems or Blind floral buttons, which greatly diminishes the production of the rose, since a floras button means a rose less than to harvest. The research aims to reduce the number of blind shoots in the production of rose bushes to increase yield of the crop